2018
DOI: 10.1016/j.tics.2018.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity Fingerprints: From Areal Descriptions to Abstract Spaces

Abstract: Fifteen years ago, Passingham and colleagues proposed that brain areas can be described in terms of their unique pattern of input and output connections with the rest of the brain, and that these connections are a crucial determinant of their function. We explore how the advent of neuroimaging of connectivity has allowed us to test and extend this proposal. We show that describing the brain in terms of an abstract connectivity space, as opposed to physical locations of areas, provides a natural and powerful fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
130
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(143 citation statements)
references
References 104 publications
13
130
0
Order By: Relevance
“…Recent efforts have developed strategies for alignment based on white matter tracts, or myelin (T1w/T2w) maps 15,16 , as well as task-based activations during movie viewing 8 . We anticipate that the joint-embedding approach used in this paper should be readily extensible to diffusion imaging data and encourage future work in this direction 75,76 . Regardless of which data modality is used, the use of a highdimensional common space may help characterize functional similarities and differences across species, particularly in areas where clear anatomical landmarks are difficult or impossible to ascertain.…”
Section: Discussionmentioning
confidence: 99%
“…Recent efforts have developed strategies for alignment based on white matter tracts, or myelin (T1w/T2w) maps 15,16 , as well as task-based activations during movie viewing 8 . We anticipate that the joint-embedding approach used in this paper should be readily extensible to diffusion imaging data and encourage future work in this direction 75,76 . Regardless of which data modality is used, the use of a highdimensional common space may help characterize functional similarities and differences across species, particularly in areas where clear anatomical landmarks are difficult or impossible to ascertain.…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing the high dimensionality of functional connectivity data, however, emerging efforts have highlighted the need for identifying summary metrics that can distill complex whole-brain connectivity data into more parsimonious sets of organizing principles. Toward this goal, a framework has been introduced to reduce such complexity into a set of dimensions describing the 'connectivity space' of the brain (Haak et al, 2018;Langs et al, 2016;Margulies et al, 2016;Mars et al, 2018aMars et al, , 2018bVos de Wael et al, 2020). Despite the value of these approaches, there is currently a lack of consensus on which method is the most applicable to develop an effective imaging biomarker.…”
Section: Introductionmentioning
confidence: 99%
“…We found that a hierarchy existed in the CFR: the CFR was relatively high in the sensory-motor networks, moderate in the dorsal and ventral attentional networks, and relatively low in the frontoparietal, default, and limbic networks. The sensory-motor networks included regions such as the motor, auditory, and visual cortices, and the association frontoparietal and default networks included regions such as the lateral prefrontal cortex and 8 temporal-parietal junction. The CFR in the sensory-motor networks was significantly (p<1e- 6) higher than that in the association networks under a two sample t-test.…”
Section: Hierarchy In the Cfrmentioning
confidence: 99%
“…Anatomical connectivity is regarded as the basis for brain functions in the cortex 7 and can provide a more powerful framework than physical location for describing brain functions 8 .…”
Section: Introductionmentioning
confidence: 99%